MANAJEMEN PEMBIAYAAN PENDIDIKAN DALAM PENGEMBANGAN MUTU DI SMK - Ariani, Atun; Pangestu, Sulung Aji; Nurfuadi, Nurfuadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to manage education financing in developing quality at SMK Muhammadiyah 1 Ajibarang Banyumas. The method used in this study is a descriptive qualitative method with data collection techniques using interviews, observations, and documentation. The data analysis technique used is qualitative analysis, namely data processing, data presentation, and initial conclusions. The results of this study indicate that: (1) Sources of education financing come from student tuition fees, alumni, and BOS funds, (2) the procedure for managing the education financing revenue budget has been made in the form of a revenue budget achievement program. These programs are based on a predetermined time period, namely: Short-term and medium-term financing revenue budget management; (3) the use of the education financing budget is adjusted to the initial management that has been made and agreed upon together based on existing guidelines or benchmarks; (4) accountability for education financing at SMK Muhammadiyah 1 Ajibarang is in accordance with management and is implemented at the end of the year. The person responsible for the use of the financing budget is the treasurer as the financial coordinator; and (5) and supervision of education financing is assigned to a special team tasked with supervising and controlling finances. The team involved in budget supervision is the community as parents of students, public relations, stakeholders, and Didasmen. ABSTRAKPenelitian ini bertujuan untuk manajemen pembiayaan pendidikan dalam pengembangan mutu di SMK Muhammadiyah 1 Ajibarang Banyumas. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriftif dengan teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Teknik analisis data yang digunakan adalah analisis kualitatif, yaitu proses data, penyajian data, dan kesimpulan awal. Hasil penelitian ini menunjukan bahwa: (1) Sumber-sumber pembiayaan pendidikan bersumber dari SPP siswa ,alumni,dan dana BOS , (2) prosedur Manajemen anggaran pendapatan pembiayaan pendidikan sudah dibuat dalam bentuk program pencapaian anggaran pendapatan. Program-program tersebut berdasarkan jangka waktu yang telah ditetapkan, yaitu: Manajemen anggaran pendapatan pembiayaan jangka pendek dan menengah; (3) penggunaan anggaran belanja pembiayaan pendidikan disesuaikan dengan manajemen awal yang telah dibuat dan disepakati bersama dengan berdasarkan panduan atau patokan yang ada; (4) pertanggungjawaban pembiayaan pendidikanm SMK Muhammadiyah 1 Ajibarang sudah sesuai dengan manajemen dan dilaksanakan pada akhir tahun. Pelaku penanggungjawab penggunaan anggaran pembiayaan di tersebut adalah bendahara selaku koordinator keuangan; dan (5) dan pengawasan pembiayaan pendidikan ditugaskan pada tim khusus yang bertugas mengawasi dan mengotrol keuangan. Tim yang terlibat dalam pengawas anggaran adalah masyarakat selaku orang tua santri, humas, stakeholders , dan Didasmen.